Stereodynamics of small 1,2-dialkyldiaziridines - Kamuf, Matthias; Trapp, Oliver (Chirality, 2013)
Diaziridines are very interesting representatives of organic compounds containing stereogenic nitrogen atoms. In particular, 1,2-dialkyldiaziridines show extraordinarily high stereointegrity. The lone electron pairs of the nitrogen atoms are in trans configuration, avoiding a four-electron repulsive interaction. Furthermore, the trans configuration of the substituents at the nitrogen atoms is energetically favored because of reduced steric interactions. Therefore only two stereoisomers (enantiomers) are observed. At elevated temperatures the enantiomers are interconverting because of the limited stereointegrity of the chirotopic nitrogen atoms. The enantiomerization rate constants and the activation parameters of interconversion are of great interest. Here, we investigated the stereodynamics of a set of small 1,2-dialkyldiaziridines bearing short substituents (Me, Et, iPr, tBu), using enantioselective dynamic gas chromatography (DGC). Separation of enantiomers of all compounds, including the highly volatile 1,2-dimethyldiaziridine, was achieved using heptakis(2,3-di-O-ethyl-6-O-tert-butyldimethylsilyl)-β-cyclodextrin in 50% PS086 (w/w) as chiral stationary phase in fused silica capillaries with a length of up to 50 m. Measurements at variable temperatures were performed and reaction rate constants were determined using the unified equation of chromatography implemented in the software DCXplorer. The activation barriers at room temperature for 1-(tert-butyl)-2-ethyldiaziridine, ΔG╪298K = 123.8 kJ mol-1 (ΔH╪ = 115.5 ± 2.9 kJ mol-1, ΔS╪ = -28 ± 1 J mol-1 K-1), and 1-ethyl-2-isopropyldiaziridine, ΔG╪298K = 124.2 kJ mol-1 (ΔH╪ = 113.1 ± 2.4 kJ mol-1, ΔS╪ = -37 ± 2 J mol-1 K-1), were determined, representing some of the highest values observed for nitrogen inversion in diaziridines. Chirality 00:000-000, 2013. © 2013 Wiley Periodicals, Inc.
Gesehen am 15.04.2021